2023
DOI: 10.3390/jrfm16100453
|View full text |Cite
|
Sign up to set email alerts
|

FinTech Adoption of Financial Services Industry: Exploring the Impact of Creative and Innovative Leadership

Muzamil Ahmad Baba,
Zia ul Haq,
Mohsina Dawood
et al.

Abstract: This paper examines the link between creative and innovative leadership and FinTech adoption through the transmission mechanisms of perceived ease of use (PEOU) and perceived usefulness (PU). This study used a questionnaire survey method to collect data from a sample of 721 employees working in the Indian financial services sector. The data were analyzed using structural equation modelling. The study results revealed a significant and positive influence of creative and innovative leadership, PEOU, and PU on Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 119 publications
5
1
0
Order By: Relevance
“…In contrast to previous hypotheses testing result, innovative leadership significantly affects the perceived usefulness. These findings corroborate the results of previous research that revealed the significant influence of innovative leadership on perceived usefulness (Baba et al, 2023;Horst et al, 2007;Leong et al, 2017;Mou et al, 2017). In accordance with this finding, innovative leadership is also proven to have significant influence on perceived ease of use.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast to previous hypotheses testing result, innovative leadership significantly affects the perceived usefulness. These findings corroborate the results of previous research that revealed the significant influence of innovative leadership on perceived usefulness (Baba et al, 2023;Horst et al, 2007;Leong et al, 2017;Mou et al, 2017). In accordance with this finding, innovative leadership is also proven to have significant influence on perceived ease of use.…”
Section: Resultssupporting
confidence: 92%
“…In addition, it is also proven that perceived ease of use significantly mediates the influence of innovative leadership digital technology use with a pvalue 0.000 < 0.05. This result is in line with Baba's research which suggests that the ease of use of technology mediates innovative leadership towards users' adoption of innovative technology (Baba et al, 2023). The findings also emphasize the importance of ease of use so that teachers are willing to use the technology introduced by their leaders.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations